2014
DOI: 10.1590/0004-282x20130220
|View full text |Cite
|
Sign up to set email alerts
|

Maternal high-fat diet during pregnancy or lactation changes the somatic and neurological development of the offspring

Abstract: The increasing prevalence of overweight and obesity is a global public health problem that affects both sexes and all age groups, especially women in reproductive age 1 . Currently 65% of the population in the world lives in countries in which obesity causes more deaths than malnutrition 2 . Moreover, the induced-high fat diet (HFD) maternal obesity has risen dramatically over the past 20 years, by nearly 42% in African-Americans and 29% in Caucasians 3 . Within this context, fetuses and newborns are increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 30 publications
4
30
0
Order By: Relevance
“…In line with previous studies, we found a decrease in fetal body weight from HFD-dams as assessed at E18, suggesting that HFD feeding might impair the intrauterine growth (Hayes et al, 2012;Mendes-da-Silva et al, 2014). In fact, Jansson and colleagues demonstrated that a reduction in the surface of the transporting epithelium in the HFD placentas might result in a decrease in the nutrient transport, thus reducing fetus weight (Jansson et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…In line with previous studies, we found a decrease in fetal body weight from HFD-dams as assessed at E18, suggesting that HFD feeding might impair the intrauterine growth (Hayes et al, 2012;Mendes-da-Silva et al, 2014). In fact, Jansson and colleagues demonstrated that a reduction in the surface of the transporting epithelium in the HFD placentas might result in a decrease in the nutrient transport, thus reducing fetus weight (Jansson et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…The present study expands on these results by demonstrating that maternal HFD feeding, regarded as a metabolic stress in the early environment, can also substantially influence adult cerebrovascular health. Consistently, maternal HFD consumption also confers susceptibility to mental health and behavioral disorders in offspring, such as depression, anxiety, impairments in social behavior, cognitive deficit, reward-based behaviors and attention-deficit hyperactivity disorder in later life (Raygada et al 1998, Bilbo & Tsang 2010, Sullivan et al 2011, Giriko et al 2013, Mendes-da-Silva et al 2014. Additionally, we demonstrated that maternal fat-rich diet influences adult depressive disorder response to stressful challenge (Lin et al 2015).…”
Section: Discussionsupporting
confidence: 69%
“…59 a SDMlard28PPPFAT, INSWalker C.D. 59 b SDMlard28YAFAT, BW, LEPNaef L. 60 SDMlard28YAFAT, BWKoukkou E. 61 SD na lard47PPPTGMendes-da-Silva C. 62 Wbothlard21YABWTaylor P.D. 63 SDFlard52 na LEPKhan I.Y.…”
Section: Resultsmentioning
confidence: 99%